The scope of state finances and their implications for combating corruption in Indonesia - Ahwan Ahwan; Yuni Ristansti (Priviet Social Sciences Journal, 2025)
The law enforcement of corruption crimes within the scope of state-owned enterprises (SOEs) continues to spark debate. The epicenter of the debate has been the use of the Business Judgment Rule (BJR) doctrine by law enforcement officials, which is considered disproportionate. A fundamental issue that has been overlooked is the scope of state finances. Excessively broad state financial regulations create grey areas and tend to contribute to chaos in law enforcement. The cases of Richard Joost Lino in 2009 and Ira Puspadewi in 2025 seem to prove that the real problem is not solely related to the use of the Business Judgment Rule doctrine, but more fundamentally to the scope of state finances. The enactment of Law Number 1 of 2025 concerning the Third Amendment to the Law on State-Owned Enterprises, which separates state finances from state-owned enterprise finances, reopens this discourse. Using normative legal research, with a legislative, conceptual, and case approach, this article seeks to respond to several criticisms that have arisen, particularly the assumption that the Law on State-Owned Enterprises will become an instrument that exacerbates corruption within the scope of state-owned enterprises. The analysis shows that several provisions in the State-Owned Enterprises Law clarify the boundaries between state finances and state-owned enterprise finances. This legal instrument is not an obstacle; rather, it provides clear guidelines for law enforcement officials to combat corruption within state-owned enterprises.